Association Between Organization Culture, Health Status, and Presenteeism. Issue 7 (July 2015) - Chang, Yao-Tsung; Su, Chien-Tien; Chen, Ruey-yu; Yeh, Ching-Ying; Huang, Pai-Tsang; Chen, Chiou-Jong; Chu, Ming
<x xml:space="preserve">Abstract</x> Objective: The aim of this study was to examine relationships of organizational culture and health behaviors with presenteeism. Method: Data of a self-reported questionnaire were collected from 816 employees, who joined the study on a voluntary basis, in seven enterprises in northern Taiwan. Results: Organizational culture and health behaviors were found to be significantly associated with presenteeism. After adjusting for confounding factors, the number of health complaints seemed to be more suitable than chronic diseases in predicting presenteeism. Conclusions: This study result implied that advantage could be taken of organizational culture and employees' health behaviors to reduce presenteeism in the workplace.